Billiards Gambling in Tengin Baru Village, Kecamatan Sepaku, Penajam Paser Utara District: Permainan Judi Biliar di Desa Tengin Baru Kecamatan Sepaku Kabupaten Penajam Paser Utara - Saputra, Muhammad Ricky; Situmorang, Lisbet (Progress In Social Development, 2020)
ABSTRACT: This article interprets the game of Billiards Gambling in Tengin Baru Village, Sepaku District, Penajam Paser Utara Regency which is done openly. The social context of the billiard gambling text can be said to be like being in a social space that is starting to open up by the influence of global economic culture, bound by the Anti-Gambling Law, average primary school education levels, the majority of followers of Islam and local tribal values ​​that also prohibit gambling. The Billiards Gambling Game is a combination of three elements, namely: (billiard sports, playing card gambling, buying and selling games). The sport of billiards gambling is used as a mode of outer settlement, art games are used as the core of the game, and both are packaged as entertainment businesses that are subject to buying and selling games. In the players' understanding, Billiards Gambling is transformed into various meanings according to subjectivity such as: hobbies, games, challenging games, professions, entertainment, fun, official games. In the text, the readers of the Biliary Gambling game get an articulation of new meanings that are not always in line with what the original author meant. ABSTRAK: Artikel ini menafsir permainan Judi Biliar di Desa Tengin Baru Kecamatan Sepaku Kabupaten Penajam Paser Utara yang di lakukan secara terang-terangan. Konteks sosial dari teks judi biliar ini bisa dikatakan seperti berada di ruang sosial yang mulai terbuka oleh pengaruh budaya ekonomi global, terikat oleh UU Anti Perjudian, tingkat pendidikan rata- rata sekolah dasar, mayoritas penganut islam dan nilai-nilai lokal suku yang juga melarang perjudian. Permainan Judi Biliar adalah perpaduan tiga elemen yaitu: (olahraga biliar, judi kartu remi, permainan jual beli). Olahraga judi biliar digunakan sebagai modus penapakan luar, permainan kartu remi digunakan sebagai inti permainan, dan keduanya dikemas sebagai bisnis hiburan yang tunduk pada permainan jual beli. Dalam pemahaman para pemain, Judi Biliar ini menjelma menjadi beragam makna menurut subyektifitas seperti: hobbi, game, permainan penuh tantangan, profesi, hiburan, iseng-isengan, permainan yang resmi. Di teks para pembaca permainan Judi Biliar mendapatkan artikulasi pemaknaan baru yang tidak selalu sejalan dengan apa maksud awal pengarangnya.